2021
DOI: 10.1016/j.jamda.2021.01.073
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Scientific Publishing

Abstract: JAMDA j o u r n a l h o m e p a g e : w w w . j a m d a . c o m

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…The principal limitation of the study is the opportunistic sampling design of the survey focus on a particular research environment, making the results difficult to generalize to other research institutions in our region or in other areas of Spain. Yet, the results obtained herein align with those reported in distant geographical areas such as the United States ( Myers et al, 2020 ; Subramanya et al, 2020 ; Sloane and Zimmerman, 2021 ). Another limitation is the low return rate for questionnaires (21.7%), but this response rate is, however, similar to that seen in other surveys of analogous study populations ( Alonso-Flores and Moreno-Castro, 2018 ; Alonso et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…The principal limitation of the study is the opportunistic sampling design of the survey focus on a particular research environment, making the results difficult to generalize to other research institutions in our region or in other areas of Spain. Yet, the results obtained herein align with those reported in distant geographical areas such as the United States ( Myers et al, 2020 ; Subramanya et al, 2020 ; Sloane and Zimmerman, 2021 ). Another limitation is the low return rate for questionnaires (21.7%), but this response rate is, however, similar to that seen in other surveys of analogous study populations ( Alonso-Flores and Moreno-Castro, 2018 ; Alonso et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…The ability to judge and evaluate a nation's scientific publication is vital for healthcare institutions, the government and even for business ventures. Internationally, it was estimated that 4% of the world's research output was devoted to the coronavirus in 2020, but 2020 also observed an exponential increase in publications on all subjects submitted to scientific journals, perhaps many researchers had to stay at home and focus on writing up papers rather than conducting science [ [17] , [18] , [19] ]. Bibliometric studies provide interesting methods for measuring the scientific value of a particular field over a specific time [ [12] , [13] , [14] ].…”
Section: Discussionmentioning
confidence: 99%
“…Journals have accelerated the peer-review process to ensure rapid dissemination of the findings and therefore have received an overwhelming number of papers on the COVID-19 pandemic. A PubMed-based search identified more than 100,000 COVID-19 articles published in 2020, leading to a ∼10% increase in the total publication numbers over 2019 [1] . The unprecedented speed and volume of publishing on COVID-19 have greatly contributed to advancing our knowledge of this pandemic and to timely guiding medical management and policy-making.…”
Section: Dear Editormentioning
confidence: 99%